MENINJAU IMPLEMENTASI DESENTRALISASI PENDIDIKAN PADA PENYELENGGARAAN OTONOMI DAERAH DI INDONESIA - man, Herman man (Makassar Journal of Social Sciences, 2013)
He regional administration in Indonesia has experienced a significant shift from centralized to the decentralized models. The change Occurs in line with the reform era and government political system after the collapse of the New Order regime in 1998. Reform of the areas of government with decentralized models embodied in the Act Nomor22 of 1999 on Local Government the which is then converted menjadiUndang-Law No. 32 Year 2004 on Regional Government, and Laws No. 25 of 1999 on Financial Balance between Central and Regional the which is then converted into Law No. 33 of 2004 on Financial Balance between the Central Government and the Local Government. The birth of two regional autonomy law aims to create regional autonomy in the framework of Kasatuan Republic of Indonesia (Sarundayang, 2003). Implications of decentralization policy is implemented a delegation of authority implementation of government affairs of the Central Government to the Government area. Through the decentralization of local government has the right to organize the implementing governmental affairs in accordance with the potential, needs and problems in Reviews their respective regions.Government Affairs under the authority of local government Consists of obligatory functions and affairs of choice. For the Government of the District / City by Law No. 32 Year 2004 on Regional Government, has the authority in 16 obligatory, whereas for business option in the law include government affairs of the which obviously exist and the potential to improve the welfare of the community in accordance with the conditions, peculiarities, and excellent potential areas of relevant education. Affairs is one of the government issues are speci regulated in Law No. 20 of 2003 on the National Education System. In Article 11 of the Act outlined that the Government and Local Government shall provide the services and facilities, and Ensure the quality of education for every citizen without diskrimianasi and Ensure the availability of funds for the implementation of education for every citizen over the age of seven to fifteen years.